Prevotella intermedia and periodontitis are associated with severe asthma. Issue 1 (16th August 2019) - Lopes, Mabel P.; Cruz, Álvaro A.; Xavier, Márcia T.; Stöcker, Andreas; Carvalho‐Filho, Paulo; Miranda, Patrícia M.; Meyer, Roberto J.; Soledade, Kaliane R.; Gomes‐Filho, Isaac S.; Trindade, Soraya C.
Abstract: Background: Periodontitis, an inflammatory disease of multibacterial etiology that affects the protective and supporting tissues surrounding teeth, can influence the course of respiratory diseases, such as asthma, due to epithelial alterations arising from inflammatory and immunological processes, bronchial remodeling, or by the aspiration of pathogenic colonizers found in periodontal pockets. This study evaluated the levels of periodontal pathogens Prevotella intermedia, Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, and Aggregatibacter actinomycetemcomitans in the subgingival biofilm of individuals with and without severe asthma. Methods: A case‐control study enrolling 457 individuals (220 with asthma and 237 without asthma) was conducted at the Program for Control of Asthma in Bahia (ProAR) Clinic located in Salvador, Bahia, Brazil. A structured questionnaire was used to obtain data on sociodemographic, health status, and lifestyle habits. A clinical periodontal assessment was performed, including bleeding on probing, probing depth, and clinical attachment level. Subgingival biofilm was collected at the deepest site of each sextant, and bacterial DNA was extracted. Quantitative real‐time PCR analysis was performed to detect and relatively quantify periodontopathogens in the biofilm. Results: Statistically significant positive associations were found between periodontitis and severe asthma, (odds ratio [OR]adjusted] : 4.00; 95% confidence interval [CI]: 2.26 to 7.10). High levels of P. intermedia were found in association with the presence of severe asthma (ORadjusted : 2.64; 95% CI: 1.62 to 4.39; P  < 0.01). Conclusions: The present results suggest that periodontitis and P. intermedia are associated with severe asthma. However, the functional consequences of this dysbiosis upon asthma susceptibility and its phenotypes remain unclear.